Islamic Political Ethics: An Analysis of Generation Z’s Views on the Practice of Risywah During Elections - Akkeu Iswara; Aliya Safitri Nurwan; Dini Fuji Amila; Salsa Nurul Fauziah; Uray Nikita Aisya Syakina; Zahra Nisfi Islami; Edi Suresman (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
General elections (Pemilu) are a crucial instrument in a democracy that adheres to a representative system. The election process must be conducted with transparency and freedom of expression. Elections should be conducted fairly and honestly, with each individual or community's political choices based on rational considerations and their conscience, not on any particular reward. However, the reality in Indonesia still shows the practice of risywah or the phenomenon of